Failure Of International Law In Case Settlement International - Hasanatul Wahida; Marcelina Deva Yanti (Institut Karya Mulia Bangsa, 2026)
This study examines the failure of international law in resolving international disputes caused by weak enforcement mechanisms, political dominance of powerful states, and ineffective sanction systems within international organizations. In principle, international law aims to maintain global order and provide peaceful dispute settlement mechanisms. However, in practice, its effectiveness is often undermined by national interests and political considerations of states. Additionally, limitations in the jurisdiction of international courts and the non-compliance of states with international rulings further weaken the effectiveness of international law. This research employs a literature study approach by analyzing relevant academic sources. The findings indicate that the effectiveness of international law largely depends on the political commitment of states and the strengthening of global enforcement mechanisms.